Cerebral salt wasting syndrome in a child with central diabetes insipidus following surgery for recurrent craniopharyngioma: A case report - Manuel André Virú-Loza (SAGE Open Medical Case Reports, 2024)
Surgical treatment of craniopharyngiomas in children can produce disorders related to water and sodium such as central diabetes insipidus (CDI) and cerebral salt wasting syndrome (CSWS). The combination of both in children is unusually reported in the literature and is associated with high mortality. The management of CSWS is based on fluid therapy. Fludrocortisone is useful in children with CSWS who do not respond to fluid management. The objective of the paper is to describe the case of 6 years and 10 months old male child with hypopituitarism secondary to a craniopharyngioma surgery performed 7 months before, who presented to the emergency department due to recurrent craniopharyngioma. The child presented a combination of CDI and CSWS following surgery for this recurrent tumor. Therapy with fludrocortisone was effective. Pediatric patients as the one of this report can help build the foundation for subsequent systematic reviews or trials.